(untitled) (Edad Media. Revista de Historia, 2023)
Bartomeu Santjust, a knight domiciled in Barcelona, died at the end of 1464. In the Historical Archive of the City of Barcelona there is a post-mortem inventory of his deeds, which includes numerous documentation related to the forty debt securities that he owned at the time of his death. There is no doubt, then, of the importance of debt in Santjust’s finances. On this basis, this article has three main objectives. Firstly, to provide a brief biography of Bartomeu Santjust in order to understand the knight’s origins and his possible motivations for entering the debt market. Next, to determine which of Santjust’s titles had originally been sold by public institutions and which ones by private bodies and individuals, as well as their respective characteristics. Finally, to see through which mechanisms Bartomeu was able to build such an impressive annuities portfolio.